Association of Chronic Pancreatitis and Malignant Main Duct IPMN: A Rare but Difficult Clinical Problem - Zoltán Berger; Hernán De La Fuente; Manuel Meneses; Fernanda Matamala; Makarena Sepúlveda; Claudia Rojas (Case Reports in Gastrointestinal Medicine)
We report the case of a 70-year-old woman who consulted for recurrent short episodes of mild-to-moderate abdominal pain. Dilated main pancreatic duct was seen on CAT scan and magnetic resonance, with multiple calcifications and intraductal stones, typical in CP. However, for a more pronounced cystic dilatation in the pancreatic head, we could not exclude the coexistence of a main duct IPMN. ERCP was performed, with pancreatic sphincterotomy and extraction of pancreatic stones, but, at the same time, mucin extrusion was seen from the dilated duct through the papilla. Pancreatoduodenectomy was performed. Surgery and histology confirmed malignant IPMN with the typical image of chronic pancreatitis and intraductal stones in the vicinity. The patient is doing well 4 years after the surgery, without recurrence of the malignant disease, with changes of chronic pancreatitis in the pancreatic remnant. This paper discusses the possible relationships between the two entities and emphasizes the need of differential diagnosis.